2021
DOI: 10.3390/app11136238
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Approach for Rainfall-Runoff Modelling Using Equilibrium Optimizer Coupled Extreme Learning Machine and Deep Neural Network

Abstract: Rainfall-runoff (R-R) modelling is used to study the runoff generation of a catchment. The quantity or rate of change measure of the hydrological variable, called runoff, is important for environmental scientists to accomplish water-related planning and design. This paper proposes (i) an integrated model namely EO-ELM (an integration of equilibrium optimizer (EO) and extreme learning machine (ELM)) and (ii) a deep neural network (DNN) for one day-ahead R-R modelling. The proposed R-R models are validated at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The EO-ELM model was compared with a Deep Neural Network (DNN) with ELM, Kernel ELM (KELM), particle swarm optimization-based ELM (PSO-ELM), SVR, ANN, and Gradient Boosting Machine (GBM). The Results demonstrated that the EO-ELM was the most accurate model 15 . Mahdavi-Meymand et al applied different kinds of GMDH that integrated with PSO and HGSO algorithms to simulate the maximum hydro-suction dredging depth.…”
Section: Introductionmentioning
confidence: 92%
“…The EO-ELM model was compared with a Deep Neural Network (DNN) with ELM, Kernel ELM (KELM), particle swarm optimization-based ELM (PSO-ELM), SVR, ANN, and Gradient Boosting Machine (GBM). The Results demonstrated that the EO-ELM was the most accurate model 15 . Mahdavi-Meymand et al applied different kinds of GMDH that integrated with PSO and HGSO algorithms to simulate the maximum hydro-suction dredging depth.…”
Section: Introductionmentioning
confidence: 92%
“…With the fast development of computer technology, ANN has been successfully applied in many fields due to its unique advantages of nonlinearity, non-convexity and self-adaptability [20][21][22]. The rainfall-runoff process is a highly nonlinear, time-varying, spatially uneven and dynamically uncertain process, and therefore ANN has been widely used to handle water resource problems such as rainfall forecasting and urban drainage systems [23][24][25]. A series of researches are used to explore the applicability of static ANNs, such as typical back propagation neural networks (BPNN) and extreme learning machines (ELM) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The runoff time series usually shows nonlinear and non-stationary characteristics [2][3][4][5]. In addition, many factors can impact the streamflow from upstream to downstream, such as tributaries, agricultural utilization, and dams; accurate runoff prediction is thus difficult and challenging [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, stationarity is a sufficient and necessary condition for establishing time series models, which makes these models difficult to capture the nonstationary of runoff time series [12]. In contrast, because of its strong nonlinear fitting ability and advantages of nonstationary series processing, the machine learning models are widely introduced into runoff forecasting research, from the Back Propagation (BP) neural network model, which was initially applied to runoff forecasting to Support Vector Machine (SVM) [1,17,18], Extreme Learning Machine (ELM) [8,[19][20][21], and other machine learning models [22,23]. However, these classical models are easy to fall into local optimum and sensitive to parameter selection.…”
Section: Introductionmentioning
confidence: 99%